Portugal, Espanha e o Atlântico - I - Isabel Maria Freitas Valente (Euro-atlântico: Espaço de Diálogos, 2019)
In this work we try to make an approach to the shared history between two brothers countries and not always friends such as Portugal and Spain and the atlantic projection that has presided over much of its historical evolution and is also an essential part of its contemporary foreign policy. A dialogue that also acquires different nuances, since the same concept of atlanticity has different connotations for Spain and Portugal. From these various perspectives, Spain and Portugal continue to have an important mission in the challenges in today's world as interlocutors and transmission belts between different global spaces. This historical evolution and the new challenges of the atlantic world are intended to be addressed in the texts of the authors presented to them in this dossier and that address very diverse historical periods from the beginning of the 20th century to the present day. Facing the most diverse possible perspectives, whether political, geostrategic, economic, social and cultural.